The Influence Of Responsiveness, Perceived Quality Mediated By Customer Satisfaction On Customer Loyalty Of Mobile Banking In Jakarta - Rosy Rahmasari; Raihanah Mazaya (Jurnal Ilmiah Wahana Pendidikan, 2023)
This paper mainly focuses on young generation as target group to find out their differential perception. This study aims to identify most influencing factors and determine their influencing power on young customer’s satisfaction and retention in mobile banking. It is a quantitative research with self-administered questionnaire as primary data collection instrument. Existing literature and published articles are reviewed as secondary data for hypothesis development. The data used in this study was a questionnaire and valid data were collected by 100 respondents. The sampling method in this study was non-probability sampling with purposive sampling technique. The testing tools used are SPSS version 25 and AMOS Structural Equation Modeling.The findings of the research revealed that responsiveness and perceived quality relative advantage have significant influence positive effect on customer satisfaction. And the latter influences loyalty. This paper contributes to a substantial improvement in the understanding of consumer satisfaction and its consequences, to measure young user’s satisfaction as the customer of mobile banking is not available in literature. So, this paper is an attempt to fill up this gap. In spite of having some limitation the research provides some practical implication for banks with better strategic insight to design mobile banking services to yield higher customer satisfaction.